18. DEVELOPMENT OF A STANDARDIZED TONGUE IMAGE DATABASE FOR TONGUE DIAGNOSIS EDUCATION AT THE FACULTY OF TRADITIONAL MEDICINE, UNIVERSITY OF MEDICINE AND PHARMACY AT HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to develop a standardized tongue image database to support the teaching of tongue diagnosis in traditional medicine. The specific objectives were: to collect high-quality, standardized tongue images; to establish diagnostic labels for the images based on expert consensus among traditional medicine specialists; and to evaluate the educational effectiveness of the standardized database on traditional medicine students after instruction.Subject and methods: A total of 120 high-quality tongue images were collected under standardized conditions. Diagnostic features were determined through consensus among five traditional medicine experts. An 80-question test was administered to assess educational effectiveness. An independent t-test was conducted to compare the overall mean scores between the student and lecturer groups, with statistical significance set at p ≤ 0.05.Results: Diagnostic labels were assigned based on majority agreement among the five experts, covering eight tongue features. A total of 132 traditional medicine students completed the diagnostic test after training with the database. The results indicated that the students’ diagnostic performance was nearly equivalent to that of the five traditional medicine lecturers.Conclusion: The study successfully established a standardized tongue image database for educational use in tongue diagnosis and demonstrated its educational utility. This database contributes to the standardization and broader dissemination of tongue diagnosis training in traditional medicine.
Keywords: Tongue diagnosis; database; medical education.